Investigating Dark Energy Equation of State With High Redshift Hubble Diagram - Demianski, Marek; Lusso, Elisabeta; Paolillo, Maurizio; Piedipalumbo, Ester; Risaliti, Guido (Frontiers in Astronomy and Space Sciences, 2020)
Several independent cosmological data, collected within the last 20 years, revealed the accelerated expansion rate of the Universe, usually assumed to be driven by the so called dark energy, which, according to recent estimates, provides now about 70% of the total amount of matter-energy in the Universe. The nature of dark energy is yet unknown. Several models of dark energy have been proposed: a non-zero cosmological constant, a potential energy of some self interacting scalar field, effects related to the non-homogeneous distribution of matter, or effects due to alternative theories of gravity. Recently, it turned out that the standard flat ΛCDM is disfavored (at 4σ) when confronted with a high redshift Hubble diagram, consisting of supernovae of type Ia (SNIa), quasars (QSOs), and gamma ray-bursts (GRBs) (Lusso and Risaliti, 2016; Lusso et al., 2019; Risaliti and Lusso, 2019). Here we use the same data to investigate if this tension is confirmed, using a different approach: actually in Lusso and Risaliti (2016), Lusso et al. (2019), and Risaliti and Lusso (2019), the deviation between the best fit model and the ΛCDM model was noticed by comparing cosmological parameters derived from cosmographic expansions of their theoretical predictions and observed high redshift Hubble diagram. In this paper we use a substantially different approach, based on a specific parametrization of the redshift dependent equation of state (EOS) of dark energy component w(z). Our statistical analysis is aimed to estimate the parameters characterizing the dark energy EOS: our results indicate (at > 3σ level) an evolving dark energy EOS, while the cosmological constant Λ has a constant EOS, wΛ = −1. This result not only confirms the tension previously detected but shows that it is not an artifact of cosmographic expansions.